SITAgliptin for Depressive Symptoms in Type 2 Diabetes: A Feasibility Randomized Controlled Trial. Issue 8 (21st October 2021) - Moulton, Calum D.; Rokakis, Anna S.; Pickup, John C.; Young, Allan H.; Stahl, Daniel; Ismail, Khalida
Abstract : Supplemental digital content is available in the text. ABSTRACT: Objective: We tested the feasibility of using sitagliptin—a dipeptidyl peptidase-IV inhibitor—for depressive symptoms in type 2 diabetes (T2D). Methods: In a feasibility, double-blind, randomized controlled trial, we recruited people aged 18 to 75 years with T2D (glycated hemoglobin A1c levels ≥53 and ≤86 mmol/mol prescribed oral hypoglycemic therapy) and comorbid depressive symptoms (Patient Health Questionnaire-9 score ≥10) from family practices in South London. Eligible patients were randomized to sitagliptin 100 mg per day or matched placebo for 12 weeks. The primary feasibility outcomes were participation rates, attrition rates, and adverse events. The primary clinical outcomes were depressive symptoms (Patient Health Questionnaire-9 and 16-item Quick Inventory of Depressive Symptomatology scores) at 12 weeks as assessed using analyses of covariance. Ranges of treatment effects were estimated using Cohen d and associated 95% confidence intervals, where negative values favored sitagliptin over placebo. Results: Of 153 people screened across 32 practices, 44 were randomized (22 to each arm). The mean (standard deviation) age was 58.8 (8.3) years, 46% were female, and 52% were of non-white ethnicity. Of those treated, 1 patient (4.5%) in each arm withdrew, and there were no group differences in adverse events. Despite improving 12-week glycated hemoglobin A1c ( d = −1.19 [95% confidence interval = −1.90 to −0.48), improvement in 12-week Quick Inventory of Depressive Symptomatology score with sitagliptin was inferior to placebo across the range of estimated treatment effects ( d = 0.71 [0.13 to 1.30]). Effects of sitagliptin on inflammation were inconsistent ( d = −0.32 [−0.81 to 0.17] for high-sensitivity C-reactive protein). Conclusions: Repositioning of oral hypoglycemic therapy for depressive symptoms in T2D is feasible. However, in this unpowered feasibility study, we did not detect evidence of superiority of sitagliptin over placebo. The results are cautioned by the small sample size and limited treatment duration. Trial Registration: EudraCT: 2015–004527-32.